2003
DOI: 10.21273/jashs.128.6.0876
|View full text |Cite
|
Sign up to set email alerts
|

Early Generation Evaluation in Antirrhinum majus for Prediction of Cutflower Postharvest Longevity

Abstract: On-plant floret longevity and cutflower postharvest longevity (PHL) of Antirrhinum majus L., snapdragon, were evaluated using inbreds P1 (16 day PHL) and P2 (6 day PHL), F1 (P1 × P2), F2 (F1 self-pollinated), F2 × F2 (among and within PHL categories: long, 17 to 25 days; middle, 9 days; and short, 2 to 3 days), and F3 families (F2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Midparent-offspring regression resulted in a heritability estimate for PHL of 0.54 ( Fig. 1 and Table 1), slightly higher than previous ANOVA-derived estimates of 0.41 (Martin and Stimart, 2003), and 0.30 (Schroeder and Stimart, 2001). Heritability of F 5 × F 5 progeny PHL derived from ANOVA was 0.77 ± 0.11 (Table 1) and comparable to A. majus inbred lines (0.79 to 0.81; Martin and Stimart, 2005), Lilium (0.74; van der Meulen-Muisers et al, 1999), and R. ×hybrida (0.80; De et al, 1999).…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations
“…Midparent-offspring regression resulted in a heritability estimate for PHL of 0.54 ( Fig. 1 and Table 1), slightly higher than previous ANOVA-derived estimates of 0.41 (Martin and Stimart, 2003), and 0.30 (Schroeder and Stimart, 2001). Heritability of F 5 × F 5 progeny PHL derived from ANOVA was 0.77 ± 0.11 (Table 1) and comparable to A. majus inbred lines (0.79 to 0.81; Martin and Stimart, 2005), Lilium (0.74; van der Meulen-Muisers et al, 1999), and R. ×hybrida (0.80; De et al, 1999).…”
Section: Resultscontrasting
confidence: 55%
“…Not all cross combinations could be evaluated due to resource limitations. Thus, a sample of 158 F 5 × F 5 progeny was chosen among and within PHL categories for evaluation of PHL and quality traits in Fall 2002and 2003. In Fall 2002, 79 F 5 × F 5 progeny, P1, P2, and F 1 (P1 × P2) were grown under standard forcing procedures (Rogers, 1992) in a polyethylene greenhouse at the Univ.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies have explored the heritability of intact floral longevity, which would be more directly relevant to the evolution of floral longevity in wild species. Of those, two demonstrated significant additive genetic effects underlying variation in intact floral longevity (Krahl & Randle, ; Howard et al ., ), while a third showed that postharvest floral longevity is positively correlated to intact floral longevity in at least one species (Martin & Stimart, ). Thus, from this limited evidence, we know that a response to selection on floral longevity is possible in at least some horticultural species.…”
Section: Introductionmentioning
confidence: 99%